Do viewers of YouTube fitness content actually exercise? : Exploring fitness video viewing, exercise intention, and exercise behaviour in Singapore - Ang, Ci Xian (Nanyang Technological University, 2021)
Social media (SM) is an integral part of daily living, especially during COVID-19. Despite increases in fitness content viewership on YouTube, Singapore’s top SM platform, and prevalent usage of YouTube in exercise promotion, its effects on physical well-being and factors contributing to promotional successes remain largely unknown. Consequently, this study aimed to explore whether YouTube fitness content viewers performed the exercises depicted and uncover the factors contributing to viewership and subsequent behaviours. It was hypothesised that more physically active viewers were more likely to perform the exercises. An online survey was conducted, gathering 200 Singaporeans or permanent residents aged 21 years or older, with minimally one YouTube account, watched YouTube fitness content minimally once in the past six months, and without cognitive disabilities. The questionnaire assessed physical activity (PA) levels via the IPAQ-SF, exercise intentions and behaviour via TPB based questions, and reasoning behind intentions and behaviours via open-ended questions. Viewers were likely to exercise during or after watching the videos (ρs = 0.51, ps < 0.001, ρr = 0.62, pr < 0.001) due to having intentions to exercise before watching. No significant relationship was identified between PA levels and exercise behaviours (ρs = 0.00, ps = 1.00, ρr = 0.00, pr = 0.87). The thematic analysis identified exercise achievability, instructor choice, music selection, and visuals as key factors affecting viewership and behaviour. Findings indicate that YouTube is a promising platform for exercise promotion but requires further research for more effective usage.